2023
DOI: 10.1177/08919887231195220
|View full text |Cite
|
Sign up to set email alerts
|

Minor Phenomena in Parkinson’s Disease–Prevalence, Associations, and Risk of Developing Psychosis

Ruth B. Schneider,
Peggy Auinger,
Roseanne D. Dobkin
et al.

Abstract: Background Minor phenomena, including passage phenomena, feeling of presence, and illusions, are common and may represent a prodromal form of psychosis in Parkinson’s disease (PD). We examined the prevalence and clinical correlates of minor phenomena, and their potential role as a risk factor for PD psychosis. Methods A novel questionnaire, the Psychosis and Mild Perceptual Disturbances Questionnaire for PD (PMPDQ), was completed by Fox Insight cohort participants with and without PD. Additional assessments in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Fox Foundation for Parkinson's Research, 2 and found a high prevalence of minor hallucinations among individuals with PD. 3 We examined the incidence of PD psychosis at 1 year and found a higher incidence rate among those with minor hallucinations (20.1, 95% confidence interval (CI), 17.2-23.0) versus without minor hallucinations (5.1, 95% CI, 4.2-6.0). Minor hallucinations were the strongest independent risk factor for incident psychosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fox Foundation for Parkinson's Research, 2 and found a high prevalence of minor hallucinations among individuals with PD. 3 We examined the incidence of PD psychosis at 1 year and found a higher incidence rate among those with minor hallucinations (20.1, 95% confidence interval (CI), 17.2-23.0) versus without minor hallucinations (5.1, 95% CI, 4.2-6.0). Minor hallucinations were the strongest independent risk factor for incident psychosis.…”
mentioning
confidence: 99%
“…Indeed, in the above work, we introduced the term "PD Mild Perceptual Disturbances" to refer to the presence of isolated minor hallucinations and the associated increased risk for psychosis. 3 We hypothesize that mild perceptual disturbances represent a transitory state associated with a higher risk of psychosis, akin to the relationship between mild cognitive impairment and dementia. We also agree that the presence of minor hallucinations alone should not prompt initiation of treatment with an antipsychotic medication or prevent adjustments in dopaminergic medications.…”
mentioning
confidence: 99%